Vanadyl-type defects in Tavorite-like NaVPO4F: from the average long range structure to local environments. Issue 47 (24th November 2017) - Boivin, Edouard; Chotard, Jean-Noël; Bamine, Tahya; Carlier, Dany; Serras, Paula; Palomares, Verónica; Rojo, Teofilo; Iadecola, Antonella; Dupont, Loïc; Bourgeois, Lydie; Fauth, François; Masquelier, Christian; et al.
Abstract : A new Tavorite-like NaVPO4 F type material with limited electrochemical performance versus its lithium analog. Abstract : Tavorite-type compositions offer rich crystal chemistry for positive electrodes in rechargeable batteries, among which LiV III PO4 F has the highest theoretical energy density ( i.e. 655 Wh kg −1 ). In this article, we report for the first time the synthesis of the related Na-based phase crystallizing in the Tavorite-like structure. Its in-depth structural and electronic characterization was conducted by a combination of several techniques, spanning electron and X-ray powder diffraction as well as infrared and X-ray absorption spectroscopy. The magnetic susceptibility measurement reveals an average oxidation state for vanadium slightly higher than V 3+ . This slight oxidation is supported by infrared and X-ray absorption spectroscopies which highlight the presence of V 4+ O vanadyl-type defects leading to an approximated NaV III 0.85 (V IV O)0.15 (PO4 )F0.85 composition. In this material, the profile of the diffraction lines is governed by a strong strain anisotropic broadening arising from the competitive formation between the ionic V 3+ –F and the covalent V 4+ O bonds. This material shows a limited extraction of sodium, close to 15% of the theoretical capacity. Indeed, its electrochemical properties are strongly inhibited by the intrinsic low sodium mobility in the Tavorite framework.